Children's response to co-branded products: the facilitating role of fit. Issue 11 (25th November 2014) - de Faultrier, Brigitte; Charry, Karine; T.M. Demoulin, Nathalie
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to represent the first empirical investigation of co-branding strategies whose target is children. It analyses such strategies' potential in the context of brand extension for non-familiar brands combined with familiar ones and provides managerial implications for both brands. Design/methodology/approach – A leisure centre-based survey was used to collect information on children's attitudes, evaluations of fit and consumption intentions of co-branded products. Findings – The findings confirm that co-branding strategies may have a very positive impact on attitudes towards partner brands, intentions to consume co-branded products and the host brand. They also indicate that consumption intentions for other products from the host product category are enhanced. From a theoretical perspective, the study stresses the essential mediating role of brand fit. Indeed, this construct appears to enable preadolescents to integrate simultaneous evaluations of two brands while constructing their attitudes towards one product. The asymmetric spill-over effect is also confirmed, with the non-familiar (weaker) brand benefiting more from the co-branding than the familiar (strong) brand. Research limitations/implications – The main limitations pertain to the small sample size and the absence of direct behavioural measures that could be added through later research. It would also be interesting to study further the concept of fit and the nature of the underlying mediating process (cognitive vs affective) among the target audience, as well as to analyse the impact of the various types of co-branding (functional vs symbolic). Practical implications – The derived guidelines suggest how non-familiar brands to the pre-adolescent target (including retailers' brand) may expand their businesses through successful alliances with a more familiar brand that is viewed favourably. Social implications – In this study, concerns were high to select a co-branded product that does not harm children's health, to the contrary (vegetable soup with cheese). The results demonstrate that the tactic may increase the target's intentions to eat products that it would not necessarily fancy (as often the case for healthy products) while contributing to the positive development of economic actors. In this, the paper shows that economic interests should not always be opposed to social welfare. Originality/value – This study investigates the very popular strategy of brand alliance among an original target (eight-to 12-year-olds) and identifies the original process through which preadolescents appraise two brands that endorse one product, a unique marketing context. This represents an important starting point to further studies on brand alliances.